PENGARUH INFLUENCER MARKETING DAN PERSEPSI HARGA TERHADAP MINAT BELI SKINCARE PADA TIKTOK SHOP - Agustin, Nurul; Amron, Amron (Kinerja, 2022)
Research on the influence of influencer marketing and price perceptions on buying interest in skincare at Tiktok Shop was made to determine the effect partially or simultaneously using quantitative methods by distributing questionnaires in the form of a Google form to 100 people. The sample in this study are users of the Tiktok application who have bought skincare at the Tiktok Shop in Semarang City. The data analysis technique used to process the data is multiple linear analysis and is equipped with classic assumption tests in the form of normality, multicollinearity and heteroscedasticity tests and is calculated using SPSS 25. This study provides information both partially and simultaneously that the influencer marketing variables and price perception has a significant relationship or influence on buying interest.